MEASURES TO COMBAT RODENT AND SUCKING PESTS OF POMEGRANATE (Academicia Globe: Inderscience Research, 2023)
This article presents the results of scientific research on the biology and harm of anorexia pests, and recommends effective combating anorexia pests in anorexia n bo' At the same time, it is possible to effectively combat anorexia pests by using small amounts of chemical oreparates against pests.